Analysis Specific and Non-Specific Parameters of African Leaf Extract (Vernonia amygdalina) from Mantup, Lamongan - Agustina Susanti , Triya; Wardhani Harahap, Hotma (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Indonesia has a wide range of biodiversity that is widely used in traditional medicine. One such plant is the African leaf ( Vernonia amygdalina ), which is known to have antidiabetic, anticancer, and antimalarial activities. To support its use as a quality and safe traditional medicine, efforts to standardize the quality of the extract are needed. This research aims to analyze the specific and nonspecific parameters of African leaf extract originating from the Mantup area, Lamongan Regency. This research is an experimental study, the method used is maceration with 96% ethanol solvent. The results showed that the specific parameter analysis of the African leaf extract had a yield of 16.24%. The characteristics of the extract were dark green color, distinctive odor, bitter taste and a viscous consistency.. Phytochemical screening tests showed positive flavonoids. For non-specific analysis, the water content was 9.6% (according to the Indonesian Herbal Pharmacopoeia standard). The total ash content of 19.5% and the acid insoluble ash content of 11.4% did not conform to the requirements. Non-conformities are caused by contamination with inorganic compounds such as soil, dust, or heavy metals, both during post-harvest and processing, and are influenced by the location where the plants are grown